Razão e retórica no Leviatã: a figura do inimigo na filosofia política de Thomas Hobbes - Junia Magalhaes Tavares (2011)
The general aim of this dissertation is to discuss the use of the word enemy in the book Leviathan of Thomas Hobbes. With this purpose, we analyzed directly the emergence of the term in the reference text in order to seek the meaning of the use of the word by the author. We tried to show that the authors choice by the word enemy is not random and plays a certain role in the work. We note the importance of the wordin persuading readers of the need of the social contract and of the risk of the body politic fragmentation. We come to the conclusion that this term has a rhetorical sense with highlight to the philosophers specific conception about the public space and the politics.